Temporary Overpessimism: Job Loss Expectations Following a Large Negative Employment Shock - Julian Emmler; Bernd Fitzenberger (Institute of Labor Economics (IZA), 2021)
Job loss expectations were widespread among workers in East Germany after reunification with West Germany. Though experiencing a large negative employment shock, East German workers were still overpessimistic immediately after reunification with respect to their job risk. Over time, job loss expectations fell and converged to West German levels, which was driven by a stabilizing economic environment and by an adaptation of the interpretation of economic signals with workers learning to distinguish individual risk from firm level risk. In fact, conditional on actual job loss risk, East German workers quickly caught up to West Germans regarding the accuracy of job loss expectations.
Keywords: D84; J64; J63; P20; 330; job loss; expectations; transition economies